Effectiveness of an after-school English program at a community childcare center in Korea - Suh, Justin; Allen, Alison; Chae, Kyunghee; Allen, Allen (English Education:Journal of English Teaching and Research, 2021)
Community childcare centers in Korea are established mainly for students from low-income family for the purpose of protecting and educating children in the community. English program is one of the most important program at the centers. This study investigated the effectiveness of an after-school English program at a community childcare center in a region of Seoul, Korea. Students registered in this English program were encouraged to participate in an online survey using a google form to fill out the questionnaire via a computer or mobile phone. Survey questions included effectiveness of the program, students’ satisfaction, and most helpful class activity for learning English. A semi-structured interview was conducted to gather students’ views on the program. Nine students among who completed online survey and volunteered for interview. Collected survey data were statistically analyzed using SAS Enterprise Guide 7.12. Final survey data set includes 11 respondents. The overall satisfaction with the after-school English program was high for both contents and effectiveness. High school students and student who participated in the program for more than six months chose the free conversation activity as the most helpful. The mean score for debates was the highest among all activities for English writing. The survey provided an opportunity for students to report their levels of satisfaction with the program. Results of this study indicate that students are satisfied with the English program at the community childcare centers overall and, that the performance of the lecturer can be categorized very well. This study provides insights into the need and direction of English education for students from low-income families. This study will serve as a basis to develop specialized and quality English programs for successful English learning of low-income students, and facilitate the continuous improvement process.